Alessandra Cirafici, Ornella Zerlenga, WordLikeSignMovie. Content switch, La scuola di Pitagora editrice, Napoli 2020 (diségno, 2021)
The pages of the book by Alessandra Cirafici and Ornella Zerlenga, immediately reveal the central theme of the reflection, that related to the ‘word’ considered in an intertwining of signs, spaces, languages and media (read more).